Health promoting properties of selected Malaysian underutilized fruits. - Azlan, Azrina; Ismail, Amin; Ibrahim, Mansor; Shakirin, Faridah Hanim; Khoo, Hock Eng (International Society for Horticultural Science, 2013)
Underutilized tropical fruits are less popular, are grown in the wild, are highly seasonal, have under-exploited potential and are not ready for commercialization. Dabai (Canarium odontophyllum Miq.) and bambangan (Mangifera pajang Kosterm.) are two examples of underutilized fruits widely grown in East Malaysia (Sarawak) and available during a specific fruiting season. Both are antioxidant-rich fruits with potential health benefits. Dabai pulp contains a high amount of fat, while bambangan pulp is juicy and fibrous. These underutilized fruits are rich in antioxidants, especially polyphenols in dabai and β-carotene and ascorbic acids in bambangan. Animal studies using different parts of dabai fruit and bambangan juice powder showed improved lipid profiles of the tested laboratory animals. Therefore these underutilized fruits possess high potential as functional fruits with excellent antioxidant rich capacity. Frequent consumption of underutilized fruits promises a good health and reduces risk of cardiovascular diseases. Future research also should be geared to develop the commercialization potential of underutilized fruits as a source of functional ingredients and supplements.